Legal analysis of the PPATK mechanism in blocking dormant accounts in money laundering (reviewed according to the theory of criminal liability) - Teguh Bagus Prabowo; Rahmat Efendy Al Amin Siregar; Muhammad Husnul (Privietlab, 2026)
This study aims to analyze the mechanism for blocking dormant accounts by the Financial Transaction Reports and Analysis Center (PPATK) in the context of preventing money laundering, as well as to examine its alignment with the theory of criminal liability. The method used is normative legal research with a statutory approach, through an examination of Law No. 8 of 2010, PPATK Regulation No. 18 of 2017, and criminal law doctrine regarding the principle of geen straf zonder schuld. The research findings indicate that the PPATK’s authority to temporarily suspend transactions constitutes a preventive administrative measure, wherein the PPATK is only authorized to request financial service providers to temporarily suspend transactions based on the results of analyses of suspicious financial transactions, rather than directly blocking accounts as a form of criminal sanction. The status of a dormant account itself is of an administrative nature and cannot serve as a basis for imposing criminal liability on its owner. However, in practice, there is a discrepancy between legal norms and their implementation, particularly regarding inconsistent procedures, a lack of transparency, and unclear criteria for designating high-risk dormant accounts. These conditions have the potential to impose restrictions on customer rights that resemble sanctions (quasi-punitive) without undergoing an adequate criminal legal process. From the perspective of criminal liability theory, this mechanism does not satisfy the element of fault (mens rea), and thus cannot be equated with criminal sanctions. Therefore, strengthened regulations, clear delineation of authority, and effective legal protection mechanisms are necessary to ensure legal certainty and the protection of customer rights.